The prognostic relevance of psychological factors with regard to participation and success in table-tennis. Issue 23 (2nd December 2018) - Martinent, Guillaume; Cece, Valérian; Elferink-Gemser, Marije Titia; Faber, Irene Renate; Decret, Jean-Claude
ABSTRACT: This study examined the prognostic relevance of self-determined motivation, coping, burnout, perceived stress and recovery experienced by 159 youth table-tennis players involved in intensive training centers with regard to their participation and success six years later. Results of ANCOVAs showed that players who still practiced at time 2 (T2; six years later; n  = 130) reported lower time 1 (T1; while they were involved in intensive training centers) amotivation (large effect), disengagement-oriented coping, sport devaluation and reduced accomplishment (moderate effects) than their counterparts who dropped out at T2 ( n  = 29). Results of ANCOVAs also showed that international ( n  = 18) and/or national players ( n  = 86) at T2 reported significantly lower T1 amotivation (large effect), disengagement-oriented coping and sport devaluation (moderate effects) in comparison to regional ( n  = 26) players at T2. Finally results of correlational analyses showed that T2 performance and/or six-year performance progress were significantly and weakly correlated with introjected and external regulations, perceived stress and perceived recovery, and significantly and moderately correlated with amotivation, disengagement-oriented coping, sport devaluation, and reduced accomplishment. Overall, this study provided insights into the role played by self-determined motivation, coping, burnout, perceived stress and recovery in the table-tennis players' dropout and performance level six years later.